Hub Criativo: economia criativa e o desenvolvimento sustentável - Seabra, Anna Paula do Nascimento (Brasil, 2021)
This report aims to present the concept of Creative Hub and its relationship with the sustainable development. In the problematization, I identify the relationship between the city of Manaus and the immensity of the Amazon forest that surrounds it and the lack of synchronism between the city and the environment environment, justifying the need for a new look at the context in which the city is inserted. In development, I present a brief history of the development of the city of Manaus and its relationship to its economic cycles. Moving on to the conceptualization of what would be sustainable development and its origin , in addition to conceptualizing what would be economy green. The next concept to be presented is the creative economy and its origin in the world, subsequent to the understanding of this concept comes the definition of Creative Hub and like this concept can be found in several activities and in different institutions in the city of Manaus. After this stage of theoretical foundation, the next stage is the analysis of case studies, in which three projects were chosen that present as the theme the creative economy and its applicability in its different formats. In the final part, I develop the territorial analysis of the location chosen for the implementation of the project and the development of a preliminary project of the architectural proposal of a Creative Hub focused on for creative economy with a focus on sustainable development that results from research carried out previously.